Making Disciples of All Nations: Membangun Pemuridan Lintas Negara dalam Era Global - Lahagu, Ardianto; Pasaribu, Jabes; Simanjuntak, Manahan Uji; Sihombing, Rame Irmaida (Jurnal PKM Setiadharma, 2025)
Abstract The Community Service activity titled "Making Disciples of All Nations" will take place from October 22 to 27, 2024, in Singapore. This event aims to equip participants from 14 countries with the skills needed for cross-national discipleship missions. With approximately 100 attendees, the program will cover the principles of Discipling Nations (DN), Making Disciples of All Nations (MDN), and Preparing My People for End Times (PET). Participants will engage in presentations, discussions, practical skills training, and the development of follow-up action plans. This comprehensive approach will help them understand how to embody Christian values within a global context. As a result, participants will be able to comprehend and devise discipleship strategies tailored to their national contexts. They will also be prepared to become effective Gospel messengers and tackle end-times challenges. This program not only enhances participants' discipleship capabilities but also guides them in contributing to national transformation and building congregations that are ready to adapt to changing circumstances.